Genetic Diversity, Natural Selection and Haplotype Grouping of Plasmodium knowlesi Gamma Protein Region II (PkγRII): Comparison with the Duffy Binding Protein (PkDBPαRII). - Mun Yik Fong; Sarah A A Rashdi; Ruhani Yusof; Yee Ling Lau (PLoS ONE)
Background Plasmodium knowlesi is a simian malaria parasite that has been reported to cause malaria in humans in Southeast Asia. This parasite invades the erythrocytes of humans and of its natural host, the macaque Macaca fascicularis, via interaction between the Duffy binding protein region II (PkDBPαRII) and the Duffy antigen receptor on the host erythrocytes. In contrast, the P. knowlesi gamma protein region II (PkγRII) is not involved in the invasion of P. knowlesi into humans. PkγRII, however, mediates the invasion of P. knowlesi into the erythrocytes of M. mulata, a non-natural host of P. knowlesi via a hitherto unknown receptor. The haplotypes of PkDBPαRII in P. knowlesi isolates from Peninsular Malaysia and North Borneo have been shown to be genetically distinct and geographically clustered. Also, the PkDBPαRII was observed to be undergoing purifying (negative) selection. The present study aimed to determine whether similar phenomena occur in PkγRII. Methods Blood samples from 78 knowlesi malaria patients were used. Forty-eight of the samples were from Peninsular Malaysia, and 30 were from Malaysia Borneo. The genomic DNA of the samples was extracted and used as template for the PCR amplification of the PkγRII. The PCR product was cloned and sequenced. The sequences obtained were analysed for genetic diversity and natural selection using MEGA6 and DnaSP (version 5.10.00) programmes. Genetic differentiation between the PkγRII of Peninsular Malaysia and North Borneo isolates was estimated using the Wright's FST fixation index in DnaSP (version 5.10.00). Haplotype analysis was carried out using the Median-Joining approach in NETWORK (version 4.6.1.3). Results A total of 78 PkγRII sequences was obtained. Comparative analysis showed that the PkγRII have similar range of haplotype (Hd) and nucleotide diversity (π) with that of PkDBPαRII. Other similarities between PkγRII and PkDBPαRII include undergoing purifying (negative) selection, geographical clustering of haplotypes, and high inter-population genetic differentiation (FST index). The main differences between PkγRII and PkDBPαRII include length polymorphism and no departure from neutrality (as measured by Tajima's D statistics) in the PkγRII. Conclusion Despite the biological difference between PkγRII and PkDBPαRII, both generally have similar genetic diversity level, natural selection, geographical haplotype clustering and inter-population genetic differentiation index.